Quantifying the impact of post‐acute sequelae of coronavirus on the cardiopulmonary endurance of athletes - Daniel Lubarsky; Daniel E. Clark; Kimberly Crum; Ashley Karpinos; Eric D. Austin; Jonathan H. Soslow (Pulmonary Circulation)
Abstract Post‐acute sequelae of Coronavirus (PASC), or Long COVID, has emerged as a critical health concern. The clinical manifestations of PASC have been described, but studies have not quantified the cardiopulmonary effects. The goal of this study was to quantify PASC cardiopulmonary changes among endurance athletes. Endurance athletes were recruited via social media; 45 met inclusion criteria, 32 had PASC and 13 were asymptomatic at 3 months (control). Comprehensive interviews were conducted to assess: cardiopulmonary symptoms at 3 months; quantitative and qualitative changes in cardiovascular endurance; exercise hours per week at baseline and 3 months; and Modified Oslo, Dyspnea, and EQ‐5D‐5L scales. All collected data was based on self‐reported symptoms. Wilcoxon rank sum compared PASC with control to distinguish the effects of PASC vs effects of COVID infection/lockdown. PASC subjects were more likely to be female (Table). The most common 3‐month symptoms in PASC were fatigue and shortness of breath. Based on self‐reported data, subjects endorsed a median decrease of 27% in cardiopulmonary endurance levels compared with 0% in controls (p = 0.0019). PASC subjects exercised less hours and had worse self‐reported health as compared with controls. PASC subjects also had significantly worse Modified Oslo, Dyspnea, and EQ‐5D‐5L scores. Of the 32 PASC patients, 10 (31%) reported a complete inability to engage in any cardiovascular endurance exercise at 3 months. PASC leads to a significant, quantifiable decrease in cardiopulmonary health and endurance.